District Education And Cultural Department Policies In Increasing Student Sports Achievement - Ismail, Razali; Abdullah, Denny Suheri; Putra, Sukardi; Sinulingga, Albadi; Akbari, Myrza (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
This study uses a qualitative research design with the type of case study research to find out information and descriptions of government policies in developing student sports achievements. Determination of research subjects to be used in this study was carried out by snowball sampling. The subjects in this study were all components of the education and culture office of Bener Meriah district, Aceh province, namely the head of the education and culture office, school principals and trainers. The data in this study were obtained based on the output of interviews using respondents. Data analysis consists of data collection, data reduction, data presentation or display, and drawing conclusions. The conclusions of this study are: (1) The policy of the Department of Education and Culture in developing student sports is by allocating funds for coaching, optimizing extracurricular sports in schools, entrusting outstanding student athletes to their home schools and increasing the competence of training physical education teachers, (2) The role of the Department of Education and Culture in the development of student sports is to be in charge of fostering student sports by designing a planned, tiered, and ideal sports nursery implementation program. (3) The strategy used by the Department of Education and Culture in the development of student sports can be done by good talent scouting, regeneration of student athletes and the development of human resource competencies for physical education teachers in sports coaching